Efficacy and safety of Ophiocordyceps sinensis in the treatment of Hashimoto’s thyroiditis: a systematic review and meta-analysis - Wei, Maoying; Ma, Wenxin; Zhang, Wenhua; Yin, Dan; Tang, Yiting; Jia, Weiyu; Jiang, Yijia; Wang, Churan; Gong, Yanbing (Frontiers in Pharmacology, 2023)
Objective: To evaluate the efficacy and safety of Ophiocordyceps sinensis (OS) for the treatment of Hashimoto's thyroiditis (HT). Methods: We searched eight databases to collect randomized controlled trials (RCTs) of OS preparations combined with a low-iodine diet or levothyroxine for HT. The search period was from inception to June 2023. Meta-analysis was performed using Revman 5.3 software after two evaluators independently screened the literature, extracted data, and evaluated the risk of bias of the included studies. The GRADE system was used to assess the certainty of evidence. Results: A total of 14 RCTs involving 1014 patients with HT were included. Meta analysis showed that OS preparations combined with a low-iodine diet were more effective in reducing TPOAb [SMD = -3.81, 95% CI (-5.07, -2.54), P < 0.00001] and TgAb [SMD = -4.73, 95% CI (-6.86, -2.61), P < 0.00001] compared to a low-iodine diet. Compared with levothyroxine treatment alone, OS preparations combined with levothyroxine further reduced TPOAb [SMD = -2.04, 95% CI (-2.82, -1.26), P < 0.00001], TgAb [SMD = -2.01, 95% CI (-2.68, -1.33), P < 0.00001], TNF-α [SMD = -3.40, 95% CI (-5.66, -1.14), P = 0.003], IL-2 [SMD = -2.31, 95% CI (-3.98, -0.65), P = 0.006], and IL-6 [MD = -4.16, 95% CI (-6.17, -2.15), P < 0.0001], and elevated FT4 [SMD = 1.34, 95% CI (0.59, 2.08), P = 0.0004], but no significant effect on FT3 [SMD = 0.83, 95% CI (-0.12, 1.78), P = 0.09] and TSH [SMD = -0.80, 2 95% CI (-1.71, 0.11), P = 0.08]. In terms of safety, three studies reported adverse reactions in 10 patients in each of the experimental and control groups. OS preparations in combination with other treatments (low-iodine diet or levothyroxine) may decrease thyroid autoantibodies and inflammatory responses in patients with HT. In HT patients with hypothyroidism, the combination of the OS preparations with levothyroxine also improved FT4. However, the quality of the included studies was generally low. Moreover, the safety of OS preparations remains unclear. Therefore, more high-quality RCTs are needed in the future to validate the efficacy and safety of OS preparations.